The impact of an industry-driven translation training program on the performance of trainee translators - Buthainah M. Al Thowaini; Mutahar Qassem (Cogent Arts & Humanities)
This study reports on a quasi-experimental study on the effect of an industry-driven online translation training program on the translator trainees’ performance across five indicators: language, accuracy, terminology, style and clarity. A pretest-posttest design is employed to explore the effect of a 60-h online industry-driven translation training course on translator trainees’ performance on translating a journalistic article. Eighteen participants engaged in a translation task after and before the intervention, using articles from Newsela. The keylogging software records the trainee’s translations before and after the treatment, tracking the trainees’ product during the pretest and posttest of translating an English journalistic article into Arabic. The text’s translations are later assessed across five indicators: language, accuracy, terminology, style and clarity. Results reveal statistically significant differences between the pretest and posttest results, demonstrating the positive effect of an online translation training program on the trainees’ performance. Given the findings, the authors recommend utilization of industry-driven online translation training courses in translation training programs, considering the trainees’ needs on the one hand and translation competence on the other.